Association between Genes Involved in Craniofacial Development and Nonsyndromic Cleft Lip and/or Palate in the Brazilian Population. (September 2016) - Machado, Renato Assis; Messetti, Ana Camila; De Aquino, Sibele Nascimento; Martelli-Júnior, Hercílio; Swerts, Mário Sérgio Oliveira; De Almeida Reis, Silvia Regina; Moreira, Helenara Salvati Bertolossi; Persuhn, Darlene Camati; Coletta, Ricardo D.
Objective: To determine the association of single-nucleotide polymorphisms (SNPs) in genes related to craniofacial development, which were previously identified as susceptibility signals for nonsyndromic oral clefts, in Brazilians with nonsyndromic cleft lip and/or palate (NSCL/P). Design: The SNPs rs748044 (TNP1), rs1106514 (MSX1), rs28372960, rs15251 and rs2569062 (TCOF1), rs7829058 (FGFR1), rs1793949 (COL2A1), rs11653738 (WNT3), and rs242082 (TIMP3) were assessed in a family-based transmission disequilibrium test (TDT) and a structured case-control analysis based on the individual ancestry proportions. Setting: The SNPs were initially analyzed by TDT, and polymorphisms showing a trend toward excess transmission were subsequently studied in an independent case-control sample. Participants: The study sample consisted of 189 case-parent trios of nonsyndromic cleft lip with or without cleft palate (NSCL±P), 107 case-parent trios of nonsyndromic cleft palate (NSCP), 318 isolated samples of NSCL±P, 189 isolated samples of NSCP, and 599 healthy controls. Main Outcome Measure: Association of alleles with NSCL/P pathogenesis. Results: Preferential transmission of SNPs rs28372960 and rs7829058 in NSCL±P trios and rs11653738 in NSCP trios ( P = .04) were observed, although the structured case-control analysis did not confirm these associations. The haplotype T-C-C formed by TCOF1 SNPs rs28372960, rs15251, and rs2569062 was more frequently transmitted from healthy parents to NSCL±P offspring, but the P value ( P = .01) did not withstand Bonferroni correction for multiple tests. Conclusions: With the modest associations, our results do not support the hypothesis that TNP1, MSX1, TCOF1, FGFR1, COL2A1, WNT3, and TIMP3 variants are risk factors for nonsyndromic oral clefts in the Brazilian population.